Moving beyond moderate-to-vigorous physical activity: the role of light physical activity during adolescence - Deborah M. Telford; Rebecca M. Meiring; Silmara Gusso (Frontiers Media S.A., 2023)
Regular physical activity is an important component of a healthy lifestyle for young people. However, an estimated 80% of adolescents globally are insufficiently active. Traditionally, health benefits were attributed only to physical activity of at least moderate intensity, and recommendations focused on achieving a threshold of moderate-to-vigorous physical activity, without consideration of other aspects of movement within the 24 h cycle. Recently, the overall daily balance of active and sedentary behaviours has gained recognition as an important determinant of health. However, the relationship between light intensity physical activity and health has not been fully explored. In this perspective paper, we discuss key challenges in defining, measuring and analysing light physical activity which have hindered the advancement of knowledge in this area. Next, we suggest three ways in which light physical activity may enhance adolescent wellbeing: firstly, by replacing sedentary behaviours to increase daily movement; secondly, by supporting the accumulation of higher intensities of physical activity; and thirdly, by providing positive experiences to facilitate lifelong engagement with physical activity. In highlighting the importance of light physical activity during adolescence, we aim to encourage critical reflection and the exploration of new approaches towards physical activity within public health and beyond.